O papel da contaminação por compostos organoclorados e metais na ecologia de macroinvertebrados bentônicos - Souto, Renata de Moura Guimarães (2014)
The Brazil, a country of continental size, comprises one of the largest water meshes and a remarkable aquatic biodiversity. Considering the fundamental role of water in the survival and health of human populations, there is an unquestionably troubling issue: the impact that the Brazilian aquatic ecosystems are undergoing, namely soil erosion, deforestation of riparian vegetation, the non-point pollution of water by residues of fertilizers and pesticides, among others. In this context this study aimed to evaluate the levels of organochlorine compounds and metals in sediments of streams in the Triângulo Mineiro region, as well as analyze the bioaccumulation of metals in trophic groups of benthic macroinvertebrates in tropical streams. Furthermore, the sediment toxicity of streams contaminated with metals was evaluated using Chironomus xanthus as a test organism. Of the 19 organochlorines analyzed, 10 were detected in the sediments of the watercourses sampled. There was no significant bioaccumulation of organochlorines in the fauna, however, this does not exclude other possible impacts of these compounds on it. Bioaccumulation of zinc, copper and magnesium was observed in aquatic insects, but no pattern of bioaccumulation was observed in trophic groups. The values for zinc were highlighted in fauna, with a high accumulation of this metal in the organisms. The sediments of the studied sites had some level of toxicity, especially in one of the points, whose mortality in the acute and chronic toxicity tests was 100%. With regard to growth, no significant diferences between treatment and control were found. The data found reflect the occurrence of impacts on watercourses studied, especially regarding the toxicity of sediment point to the need for monitoring and even conducting future research dealing other possible toxic substances present in these sediments.